2009
DOI: 10.1177/1557988309358443
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity in Nontraditional Occupations: Ecological Constructions

Abstract: The authors present Bronfenbrenner's ecological model as a conceptual framework to explore interlocking systemic and interpersonal influences on the development and perpetuation of men's gender role-related distress. To demonstrate the utility of this model, the authors present results from an exploratory qualitative study of men in nontraditional occupations. Using the constant comparison method, the authors' analysis of multiple interviews with elementary educators and medical support staff unearthed interwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
15
1
2
Order By: Relevance
“…Women, in contrast to men have a higher possibility to continue working especially if they are married or working at home. Retirement is souldestroying for men, because according to many men, work symbolises masculinity (Shen‐Miller 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Women, in contrast to men have a higher possibility to continue working especially if they are married or working at home. Retirement is souldestroying for men, because according to many men, work symbolises masculinity (Shen‐Miller 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the impact of stereotypes on male nurses' experiences represents one site in which such theories could expand the existing literature. As another example, notions of masculinity could affect client and employer beliefs about the care that male nurses are capable of providing (e.g., Simpson 2009), as well as policies for hiring, promotion, and distributing job duties (e.g., scheduling all female clients with female nurses; Shen-Miller et al 2011;Simpson 2004;Williams 2013). Similarly, expanding inquiries of men's experiences to more occupations can deepen understanding of important concepts such as tokenism; some researchers (e.g., Simpson 2009;Williams 2013) have found that although men's experiences as tokens are embedded in the gender privilege afforded to men in society at large, those men often sometimes employ gender based privilege in different ways, such as marginalizing themselves from female peers (consistent with notions underlying gender role conflict such as avoidance of the feminine).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In addition, these influences come from all socialization agents (family, teachers, school, media, laws, etc.) (Shen-Miller et al, 2011;Baker et al, 2016;Paul Halpern and Perry-Jenkins, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, an asymmetry of gender stereotypes exists: gender stereotyping is less restrictive for female stereotypes than for male stereotypes (Wilbourn and Kee, 2010;Siyanova-Chanturia et al, 2015). In addition, several studies indicate that girls generally show more flexible gender stereotypes than boys (Shen-Miller et al, 2011;Siyanova-Chanturia et al, 2012), especially in the area of domestic activities (Poulin-Dubois et al, 2002).…”
Section: Introductionmentioning
confidence: 99%